2013
DOI: 10.1177/156482651303400102
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Physical Activity, Sedentary Behaviors, and Dietary Habits to the Prevalence of Obesity among Kuwaiti Adolescents

Abstract: Background. The increasing rate of obesity among Kuwaiti adolescents is associated with immediate and long term-risks to their health and well-being.Objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
69
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 40 publications
(44 reference statements)
10
69
1
Order By: Relevance
“…Overweight and Obesity are associated with sedentary behaviour [26], and over-nutrition [27, 28] while underweight is partly related to undernutrition [29]. Neither of them (underweight, overweight or obesity) is a desirable health status and constitutes the extremes of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and Obesity are associated with sedentary behaviour [26], and over-nutrition [27, 28] while underweight is partly related to undernutrition [29]. Neither of them (underweight, overweight or obesity) is a desirable health status and constitutes the extremes of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the validation of the physical activity questionnaire and data collection procedure have been described elsewhere (20,21) . The questionnaire was designed to collect information on frequency, duration and intensity of a variety of light-, moderate-and vigorous-intensity physical activities during a typical week.…”
Section: Physical Activity Assessmentmentioning
confidence: 99%
“…The physical activity questionnaire covered all domains of physical activity such as transport and household, fitness and sports activities. Physical activities were assigned metabolic equivalent of task (MET) values based on the compendium of physical activity (25) and the compendium of physical activity for youth (26) as described in detail elsewhere (20) . Briefly, the moderate-intensity physical activity includes activities such as normal-pace walking, brisk walking, recreational swimming, household activities and moderate-intensity recreational sports such as volleyball, badminton and table tennis.…”
Section: Physical Activity Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This current epidemic of childhood obesity is largely due to an environment that promotes excessive food consumption and encourages sedentary behaviors [22]. The diet of Arab adolescents is characterized by a low intake of fruit, vegetables, and milk and a high intake of sugar-sweetened beverages, fast foods, and sweets [3,5,8]. The prevalence of overweight and obesity in children in the United Arab Emirates (UAE) is extremely high; the Global School Health Survey (GSHS) 2010 reported that approximately 40% of school children are overweight or obese.…”
Section: Introductionmentioning
confidence: 99%